2016
DOI: 10.4149/bll_2016_073
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 4-MEI on cell proliferation, DNA breaking and DNA fragmentation

Abstract: 4-Methylimidazole (4-MEI) is a color widely found in cola drinks, roasted foods, grilled meats, coffee and other foods. This study was aimed to investigate the 4-MEI effects on the cell proliferation, purifi ed circular DNA and DNA from cells of rats treated with the 4-MEI. In this study, mouse 3T3-L1 cell line was treated with 4-MEI at concentrations of 300, 450, 600 and 750 μg/mL for 24 hours and 48 hours periods, after that cytotoxic effect of the 4-MEI was studied by MTT test. Also, the effect of 4-MEI on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Edenharder and Tang, who observed the antimutagenic effect of purpurin, alizarin and other 10 anthraquinone compounds using the Ames test [21]. Similar results were obtained by Rayes who found the Cola soft drink had toxic effect on the mice testicular cells [22][23][24]. According to our and other researcher's results, some of food dyes usually induce genotoxicity.…”
Section: Commentarysupporting
confidence: 82%
“…Edenharder and Tang, who observed the antimutagenic effect of purpurin, alizarin and other 10 anthraquinone compounds using the Ames test [21]. Similar results were obtained by Rayes who found the Cola soft drink had toxic effect on the mice testicular cells [22][23][24]. According to our and other researcher's results, some of food dyes usually induce genotoxicity.…”
Section: Commentarysupporting
confidence: 82%
“…Saito et al [24] who found that in Chinese hamster 79 cells, bupropion hydrochloride caused DNA single strand breaks and decrease in the DNA and RNA content. In addition, Jefferson et al [25] observed that bupropion produced positive response (2 to 3 times control mutation rate) in 2 of 5 strains in the Ames bacterial mutagenicity test [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the reaction mixture was analyzed by 1 % agarose gel electrophoresis for 45 min at 110 volts. DNA bands (supercoiled, linear, and open circular) were stained with ethidium bromide and were analyzed [21]. To understand the drug's ability to break DNA in the presence of CuCl2, 0.5273 µmole bp of pET22 plasmid DNA having 0.003 µmole CuCl2 2H2O treated with a different amount of Escitalopram (0.28, 0.14, 0.014, 0.0014, 0.00014 µmole) for 1 h and were subjected to 1 % agarose gel electrophoresis.…”
Section: Preparation Of Dnamentioning
confidence: 99%